Evaluation of service accuracy in novice tennis athletes at PELTI pangkep: Quantitative study of the hewitt test - Aprilo, Ians; Arfanda, Poppy Elisano; Mappaompo, M Adam; Yasriuddin, Yasriuddin; Awaluddin, Awaluddin; Yusnadi, Yusnadi; Priambodo, Anung (Jurnal Ilmu Keolahragaan, 2025)
Background. Accuracy in serving contributes to an athlete's game consistency, making them more unpredictable for opponents. This not only affects the technical aspect but also the psychological one, as players with accurate serves are able to maintain mental pressure on the opponent, which can ultimately change the dynamics of the match. Objectives. This research evaluates service accuracy in beginner tennis athletes at PELTI Pangkep, an aspect often overlooked in sports literature. The research gap lies in the lack of studies concerning service accuracy, especially among beginner athletes. The research aims to measure tennis service accuracy. Methods. This research is a quantitative descriptive study with a survey design conducted on January 23, 2024, involving 20 beginner tennis athletes aged 10"“18 years at PELTI Pangkep, selected through purposive sampling. The instrument used was the Hewitt Test to evaluate serves, performed with 3 trials and 10 scored serves. The data was then analyzed descriptively to calculate the mean, standard deviation, and distribution of the test results. Results. The results show that 1 athlete or 5% were in the high category, 5 athletes or 25% in the medium category, 4 athletes or 20% in the low category, and 10 athletes or 50% in the very low category, with an average score of 27.85. Conclusion. The conclusion of this research indicates that the service accuracy of beginner tennis athletes at PELTI Pangkep is still low, with most athletes in the very low category. This research contributes to the development of more effective training methods for beginner athletes.